Simplificação de Expressões Booleanas

Exemplo: ~(A * B) * (~A + B) * (~B + B) = ~A

~(A * B) * (~A + B) * (~B + B)
~(A * B) * (~A + B) Complemento, Elemento Neutro.
(~A + ~B) * (~A + B) Lei DeMorgan
~A + ~B * B Distributividade.
~A Complemento, Elemento Neutro.

Idempotência
A * A = A
A + A = A
Associatividade
(A * B) * C = A * (B * C)
(A + B) + C = A + (B + C)
Comutatividade
A * B = B * A
A + B = B + A
Distributividade
A * (B + C) = A * B + A * C
A + (B * C) = (A + B) * (A + C)
Elemento Absorvente/Neutro:
A * 0 = 0 || A * 1 = A
A + 1 = 1 || A + 0 = A
Complemento
A * ~A = 0
A + ~A = 1
Involution Law
~(~A) = A
Lei de DeMorgan
~(A * B) = ~A + ~B
~(A + B) = ~A * ~B

-----TABUÁDA BOOLEANA-----
A*0 = 0
A*1 = A
A*A = A
A*/A= 0
A+0 = A
A+1 = 1
A+A = A
A+/A= 1
//A = A
A+AB = A
A+/AB= A+B
(A+B)(A+C)=A+BC

---------------------------------------